Arabic Language Curriculum as a Foundation for Strengthening Religious Education in Public Higher Education - Rekan, Abd Aziz; Howell, Hafeezur Rahman; Mohamad Salleh, Muhamad Nasir; Rosin, Nurhasfirah; Tabrani ZA; Ma`arif, Muhammad Anas; Adnan, Mohamad Azrien Mohamed (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study was conducted to examine the implementation of the Arabic Language Program (ALP) and to explore how Arabic functions as a foundational medium for the acquisition of Islamic knowledge at a public higher education institution in Malaysia. Design/methods/approach – This study employed a mixed-method exploratory design in two phases. The first phase involved qualitative data collection through semi-structured interviews with 46 informants, classroom observations of two classes and document analysis. These findings were used to construct a quantitative questionnaire, which was then administered in the second phase to 184 respondents. The data were analyzed thematically and statistically with triangulation to ensure depth and validity. Findings – The study identified three overarching themes: (i) Towards a Dynamic Arabic Language Curriculum for Holistic Islamic Education, (ii) A Curriculum That Meets the Pedagogical Needs of Arabic Language and Religious Learning and (iii) Challenges in the Execution of the ALP Curriculum. Research implications/limitations – While the findings indicate that ALP has effectively supported students’ progress in Islamic studies, the long-established structure of the curriculum may give benefit from greater responsiveness to current educational and industrial needs. Therefore, it is recommended that further studies be conducted to explore lecturers’ perspectives and post-program outcomes in order to assess its long-term impact and sustainability. Originality/value – This study provides an in-depth evaluation of a 40-year-old Arabic preparatory program, emphasizing its role in strengthening Islamic education and identifying key areas for reform. It offers a valuable framework for enhancing Arabic language curriculum in higher education, particularly for non-native speakers especially in Southeast Asia, in support of religious educational objectives.